Divorce, indicator of social and family transformation with differential impact between sexes: study under taken in Nuevo Leon - TAMEZ-VALDEZ, Blanca Mirthala; RIBEIRO-FERREIRA, Manuel (Papeles de Población; Vol. 22 Núm. 90 (2016), 2018)
This document presents an analysis of divorce as a social and family phenomenon, centered on the main effects observed and their differential impact in men and women. For the analysis, the principal data from a study of divorce undertaken in Nuevo León was utilized. This data’s characteristics, according to demographic transition theory, constitute an indicator of the social and family transformation observed in recent decades. The analysis was based on the Theory of Social Structuration and Praxis proposed by Giddens (1984) and deepens in the resources (authoritarian and distributive) indicated by the groups, as well as their relation to the impact observed after divorce. In addition, the levels of autonomy and well-being observed among the women responsible for raising children were examined.